2013
DOI: 10.1016/j.meatsci.2012.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of raw hams using SELDI-TOF-MS to predict the final quality of dry-cured hams

Abstract: The relationship between protein profiles of Gluteus medius (GM) muscles of raw hams obtained from 4 pure breed pigs (Duroc, Large White, Landrace, and Piétrain) with the final quality of the Semimembranosus and Biceps femoris muscles of dry-cured hams was investigated. As expected, Duroc hams showed higher levels of marbling and intramuscular fat content than the other breeds. Piétrain hams were the leanest and most conformed, and presented the lowest salt content in dry-cured hams.Even if differences on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Previous studies with different breeds showed that breed and muscle type did not affect the number of peaks per spectrum in SELDI-TOF experiments, while a few of these peaks indicated muscle fibre type-specific proteins (Mach et al, 2010). Marcos et al (2013a, b), comparing four different pure breeds (Duroc, Large White, Landrace, and Pietrain) using the same technique, showed associations between protein peaks and meat quality traits, mainly water-holding capacity and texture. Although explaining a limited proportion of the variability, the authors concluded that the results showed interesting relationships between protein expression and longissimus meat quality traits.…”
Section: Biomarkers For Resources For High-quality Dry-cured Ham Prodmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous studies with different breeds showed that breed and muscle type did not affect the number of peaks per spectrum in SELDI-TOF experiments, while a few of these peaks indicated muscle fibre type-specific proteins (Mach et al, 2010). Marcos et al (2013a, b), comparing four different pure breeds (Duroc, Large White, Landrace, and Pietrain) using the same technique, showed associations between protein peaks and meat quality traits, mainly water-holding capacity and texture. Although explaining a limited proportion of the variability, the authors concluded that the results showed interesting relationships between protein expression and longissimus meat quality traits.…”
Section: Biomarkers For Resources For High-quality Dry-cured Ham Prodmentioning
confidence: 81%
“…Surprisingly, they concluded that even if differences in the quality traits (colour, water activity, texture, composition, IMF, and marbling) of dry-cured hams were observed among the studied breeds, only small differences in the sensory attributes were detected. However, associations between protein peaks and meat quality traits, mainly colour (Minolta b * , meat yellowness) and texture (for details see Marcos et al, 2013a, b), were observed. Candidate protein markers for the quality of processed dry-cured hams were identified (Marcos et al, 2013b).…”
Section: Biomarkers For Resources For High-quality Dry-cured Ham Prodmentioning
confidence: 99%
“…This has made TOF-MS an essential instrument for food analysis applications-typically with matrix-assisted laser desorption/ionization (MALDI) and ESI ionization-particularly with the development of high-resolution and hybrid instruments [quadrupole time-offlight (QqTOF), ion-trap time-of-flight (IT-TOF), and TOF-TOF configurations]. These hybrid instruments benefit from the versatile ability of quadrupoles to carry out various tasks and from the high performance of TOF spectrometers in both MS and MS/MS modes [42][43][44][45][46][47]. The QqTOF is a hybrid quadrupole TOF mass spectrometer with MS/MS capability.…”
Section: Time-of-flight (Tof)mentioning
confidence: 99%
“…Raf. and their bioactivities [92] LC-QqTOF Comprehensive characterization of bioactive phenolic compounds in cucumber whole fruit extract [93] LC-QqTOF Migration of nonintentionally added substances from adhesives and the role of EVOH to avoid migration in multilayer packaging materials [94] SELDI-TOF Analysis of raw hams to predict the final quality of dry-cured hams [43] …”
Section: Type Application Referencesmentioning
confidence: 99%
See 1 more Smart Citation